SURVEI PENDAHULUAN SEBELUM MENERAPKAN MODEL PEMBELAJARAN KOOPERATIF TEAMS GAMES TOURNAMENT (TGT) BERBANTUAN WORDWALL PADA SISWA KELAS VII SMP - Aldita Tasya Astuti; Zulirfan Zulirfan; Ernidawati Erlisnawati (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2022)
Abstract: Science learning outcomes achieved by students in Indonesia are low, determined by many factors. This study aims to determine the implementation of science learning in schools seen from the learning media factors, teaching methods used by teachers, and students' perceptions of learning science. The type of research used is quantitative descriptive research. This research method is a survey. This survey was given to students with a population of 168 students and the sample used was 47 students. Data was collected using a questionnaire with 3 questions. The results showed that 61.7% of students considered learning science in junior high school to be difficult, 70.2% of students were taught using the lecture method, and 29.6% of students were taught using learning media in the form of pictures. It can be concluded that the factors of learning media and learning models used can affect student learning outcomes.Keywords: Student Perceptions, Learning Media, Learning Models, Preliminary Survey